2020
DOI: 10.35848/1882-0786/ab998e
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability and impact of water on CsSnI3 perovskite

Abstract: Practicability of CsSnI3 has been limited by the lack of stability in humid environment. Here we calculated phase stability, the impact of H2O embedded in CsSnI3 and surface adsorption by the first-principles calculations. Total energy results show that γ-CsSnI3 and Y-CsSnI3 are more stable. However, the γ-CsSnI3 is hydrophilic-like and Y-CsSnI3 is hydrophobic-like. γ-CsSnI3 studies show that H2O tend to adsorb at the hollow sites on the (001) surface. Strong coupling between O and Cs atoms and hydrogen bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…We examine the effect of the isolated H 2 O molecule on the phase transformation to understand the moisture-induced phase instability . Many of the previous DFT studies focused on the interaction of H 2 O with surfaces of metal halide perovskites and its effect on the phase stability. However, the effects of H 2 O molecules in the bulk system and their impact on the phase stability have not been well studied. Figure a shows the optimized structures of H 2 O in γ- and δ-CsPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…We examine the effect of the isolated H 2 O molecule on the phase transformation to understand the moisture-induced phase instability . Many of the previous DFT studies focused on the interaction of H 2 O with surfaces of metal halide perovskites and its effect on the phase stability. However, the effects of H 2 O molecules in the bulk system and their impact on the phase stability have not been well studied. Figure a shows the optimized structures of H 2 O in γ- and δ-CsPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the surface energy of the γ-CsSnI 3 slab sliced along (202) terminated by Cs + and I − ions (2.6 meV/Å 2 ) was smaller than that terminated by Sn 2+ ions (23.1 meV/Å 2 ), which is consistent with the reported works. 23,37,38 Therefore, the models terminated by Cs + and I − ions were used in the current work. The thickness of the slab was set as 7 octahedral layers (i.e., 15 atomic layers), and a 16 Å vacuum layer was added above the slab to minimize the interaction with the mirror images.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…Several computational studies have been conducted to understand the compositional effect on the water adsorption properties of halide perovskites. 28,62,[80][81][82] Li et al 62 performed a comprehensive study using DFT to investigate the effect of composition on water absorption and understand their underlying mechanism by varying A = MA + , FA + and CS + ; B = Pb 2+ , Sn 2+ ; X = I À and Br. Figure 2 shows the description of various adsorption sites along with the comparison of adsorption energies for different compositions for AI and BX 2 terminated surfaces.…”
Section: Compositional Effectsmentioning
confidence: 99%